Effect of drying and storage on the degradation of carotenoids in orange-fleshed sweetpotato cultivars - Bechoff, Aurélie; Westby, Andrew; Owori, C; Dhuique-Mayer, Claudie; Menya, G.; Dufour, D.L.; Tomlins, Keith I. (Wiley, 2009)
BACKGROUND: Orange-fleshed sweetpotato (OFSP) can be used to tackle vitamin A deficiency, a major public health problem in most developing countries. In East Africa, common ways of using sweetpotato include drying and subsequent storage. The aim of the study was to investigate the impact of drying and storage on the total carotenoid retention (as an estimate of provitamin A retention) from OFSP.